Introduction to chemistry - Williams, Arthur L.; Embree, Harland D.; DeBey, Harold J. (Massachusetts: Addison-Wesley, 1968)
Inorganic chemistry: The science of chemistry - Methods of measurement - Fundamental concepts of chemistry - The structure of matter - The elements and the periodic table - Compunds and chemical bonds - Chemical equations - Oxigen - Hydrogen - Water - Solutions - Acids, basses, salts and ionization - Equilibrium - Colloids - The atmosphere: nitrogen and the noble gases - The properties of gases - The halogens - Other nonmetals - The metals - Radioactivity and nuclear chemistry. Organic chemistry: The nature of organic compounds - Saturated hydrocarbons: the alkanes - Unsaturated hydrocarbons: alkenes and alkynes - Armatic hydrocarbons: benzene and related compounds - Alcohols, phenols and eters - Organic acids - The chemistry of fats - Amines - Carbonyl compounds - Polymers - Stereosomers. Biochemistry: Introduction to biochemistry - The chemistry of carbohydrates - Proteins - Chemistry of the lipids - Chemistry of the nucleic acids - Biochemical reactions - Metabolism of carbohydrates - Metabolism of proteins - Metabolism of lipids - Nutrition - The chemistry of heredity - Biochemistry of plants - The biochemistry of disease and therapy
Keywords: QUIMICA INORGANICA; QUIMICA ORGANICA; BIOQUIMICA